Slade Green Goes Marching On - Kargotis, Demetrios; Macdonald, Dash; Mortimer, Nicholas (My University, 2023)
Slade Green Goes Marching On, is a research-led participatory performance project developed by Post Workers Theatre in collaboration with Three Rivers Bexley and the community of Slade Green Knights F.C. The project explores alternative approaches to community engagement through the collective creation and performance of football chants as a form of social and political expression. Responding to the loss of community infrastructure, including the historic Small Glen stadium, the project draws on methods from workers’ theatre, verbatim performance, and participatory design to document and activate local experiences of precarity, resilience, and collective identity. Through interviews and sustained engagement with players, parents, and coaches, verbatim testimonies were transformed into chants, banners, and performative interventions. These were enacted within training sessions and football matches, reframing grassroots sport as a site for civic dialogue and collective organisation. The project demonstrates how familiar cultural forms, such as football supporter culture, can be reimagined as tools for community mobilisation, storytelling, and political agency.
Keywords: Design activism; Participatory design; Football chants; Grass roots football; Slade Green; Three Rivers Bexley; Post Workers Theatre